FAMILY SOCIOECONOMIC DIFFERENCES AMONG CHILDREN LIVING WITH OVERWEIGHT AND OBESITY IN NORTH MACEDONIA - Stamenova, Aleksandra; Wallace, Silver Lorraine; Mihajlova, Katerina; Dimitrievska, Ljubica; Spiroski, Igor (Institute of Public Health of the Republic of North Macedonia, 2024)
Globally, the prevalence of overweight and obesity is increasing among children and adolescents. Halting the rise in obesity is a significant challenge because of the complex interplay of factors and influences. We aimed to explore the role of family socioeconomic status (SES) indicators in relation to overweight and obesity prevalence rates among primary school children in North Macedonia. Materials and methods: Data were collected on a nationally representative sample of children and their parent(s)/caregiver(s) participating in the 6th round of World Health Organization (WHO)-European Childhood Obesity Surveillance Initiative (COSI) in North Macedonia. Every child had their height and weight objectively measured and their family sociodemographic and SES data were obtained through a self-reported record form by their parent(s)/caregiver(s). According to COSI reporting, responses on three SES indicators (parental educational attainment, parental employment status and family-perceived wealth) were categorized in levels for data analysis. Overweight and obesity rates were estimated based on 2007 WHO growth references. Pearson’s χ2-tests, corrected with the Rao-Scott method, were used to test differences in overweight and obesity across various subgroups. Results: The sample consisted of primarily native-born children (97.3%) and parents (mothers - 96.2%; fathers - 97.6%), living in urban areas (66.9%), in two-parent families (84.9%) and spoke Macedonian at home (59.8%). The majority of children lived in families with low to medium SES level. Prevalence of overweight was 30.5% [95% CI: 28.5-32.7], whilst of obesity 14.1% [95% CI: 12.3-16.0]. There were no significant differences observed across family SES indicators in overweight or obesity rates. Conclusion: Our findings contribute towards reporting on family SES among children living with overweight and obesity to better understand and address potential obesity risk factors. Future research should focus on exploring family SES within the long-term context of children’s health-related behaviours.
Keywords: childhood obesity; socioeconomic status; health inequalities; WHO-COSI